Investigation on the CBM Extraction Techniques in the Broken-Soft and Low-Permeability Coal Seams in Zhaozhuang Coalmine - Zhaoying Chen; Xuehai Fu; Guofu Li; Jian Shen; Qingling Tian; Ming Cheng; Yue Wang (Geofluids)
To enhance the coalbed methane (CBM) extraction in broken-soft coal seams, a method of drilling a horizontal well along the roof to hydraulically fracture the coal seam is studied (i.e., HWR-HFC method). We first tested the physical and mechanical properties of the broken-soft and low-permeability (BSLP) coal resourced from Zhaozhuang coalmine. Afterward, the in situ hydraulic fracturing test was conducted in the No. 3 coal seam of Zhaozhuang coalmine. The results show that (1) the top part of the coal seam is fractured coal, and the bottom is fragmented-mylonitic coal with a firmness coefficient value of less than 1.0. (2) In the hydraulic fracturing test of the layered rock-coal specimens in laboratory, the through-type vertical fractures are usually formed if the applied vertical stress is the maximum principal stress and is greater than 4 MPa compared with the maximum horizontal stress. However, horizontal fractures always developed when horizontal stress is the maximum or it is less than 4 MPa compared with vertical stress. (3) The in situ HWR-HFC hydraulic fracturing tests show that the detected maximum daily gas production is 11,000 m3, and the average gas production is about 7000 m3 per day. This implies that the CBM extraction using this method is increased by 50%~100% compared with traditional hydraulic fracturing in BSLP coal seams. The research result could give an indication of CBM developing in the broken-soft and low-permeability coal seams.